Role of LBX1 rs11190870 polymorphism in adolescent idiopathic scoliosis in the Acehnese population: A preliminary study - Aulia, Teuku N.; Gatam, Luthfi; Yaman, Aman; Djufri, Djufri (Narra J, 2025)
Genome-wide association studies (GWAS) have identified the single nucleotide polymorphism (SNP) rs11190870 near the ladybird homeobox 1 (LBX1) gene as being associated with the susceptibility and severity of adolescent idiopathic scoliosis (AIS). However, no such genetic studies have been conducted in the Indonesian population. The aim of this study was to investigate the genetic profile of AIS patients in the Acehnese population, with a focus on LBX1 rs11190870, and to assess its association with disease severity. A total of 30 female AIS patients were included. Genetic analysis was performed to determine the rs11190870 genotype in each subject. The association between rs11190870 and curve progression, measured by Cobb angle, was analyzed using the Mann–Whitney U test. The T allele was found to be more prevalent (73.3%), with the TC genotype being the most common (53.3%). A significant association was observed between LBX1 rs11190870 and curve progression, where patients with the TT genotype exhibited a larger Cobb angle compared to those with TC or CC genotypes (p=0.01). This is the first study to characterize the genetic profile of AIS and its association with curve severity in the Acehnese population. These findings suggest that LBX1 rs11190870 may act as a disease modifier in AIS. Further studies with larger sample sizes are warranted to confirm the role of LBX1 rs11190870 in AIS susceptibility and severity in the Indonesian population.